Investigation of THz frequency shaped anode planar Gunn diodes operating in delayed mode - Mindil, Ahmed; Dunn, Geoffrey; Khalid, Ata; Oxley, Chris (IEEE, 2020)
A novel planar design of Gunn diode with a shaped anode contact, utilizing Monte Carlo simulations, has been shown to have produced 0.3 THz frequency current output when operated in delayed mode. Two novel anode designs are investigated here, one with two fixed distances, and the other with three fixed distances between the cathode and anode electrodes. The corresponding waveforms generated, show two and three current peaks respectively. The work suggests high frequency and novel wave-shaping applications are possible in such devices.
Keywords: Gallium arsenide; THz frequency; multiple peaks; Monte Carlo simulation; delayed mode; planar Gunn device